The Impact of Electronic Publishing on Academic Libraries - Hickey, Thomas B. (DESIDOC Journal of Library & Information Technology, 2002)
As a result of the availability of electronic publications, the libraries have the option of not subscribing to their printed versions. The paper discusses the transformation of academic libraries with such technological changes and why it is occurring now. It also discusses the impact of the World Wide Web and the role of publishers in the electronic world. It also discusses the role of the librarian and the library in future. http://dx.doi.org/10.14429/dbit.16.1.3169